Maritime Pine stress-laminated timber bridges: losses of prestress forces and flexural behavior - Jorge, L. (2011)
This article presents a study on stress-laminated timber bridges. The technique is useful for the rehabilitation and construction of bridges. It consists of a series of timber planks placed side by side and compressed transversely with highstrength steel prestressing bars. A prototype of this kind of structure was built in the Department of Civil Engineering at the University of Coimbra. The prototype, a stress-laminated timber bridge deck with butt joints, was 6 m long, 2.7 m wide, and 0.20 m thick. The experimental program was developed with two main objectives: to study the evolution of the prestress value applied to the structure and to observe the bridge structural behavior under the effect of loads simulating the action of a standard vehicle. Practical difficulties and/or limitations and potentialities of the system when maritime pine is used as the timber material are also discussed. This article reports the experimental program and the results, with emphasis on the tension losses in the prestressed steel bars.